Sleep and Women's Health - Dolev, Zippi (Milton : CRC Press LLC, 2019)
Why is it that women suffer far more than men from insomnia? What is the connection between the hormonal changes that a woman undergoes during her lifetime, and difficulty in falling asleep? What is the effect of cell phones on sleep? Should women engage in sports before going to sleep? What do women primarily dream about? In which country do people sleep the most? How do depression and anxiety affect sleep? And why is it inadvisable to resort to a "little pill" to provide unworried sleep? This clear and readable book, illustrated with short quotations of poetry and prose about sleep and dreams, provides a glimpse into the wonderful mechanism of sleep, explains how correct treatment of sleep disturbances results from understanding their causes, and shows the right path to a pleasant and satisfying night's sleep; it will be of great interest for all women and clinicians dealing with female patients. In particular, because of the connection between sleep and hormones, problems with sleep have repercussions for women's reproductive life cycle. This pioneering text will therefore be of particular interest to gynecologists working in Reproductive Medicine.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Sleep disorders; Women -- Health and hygiene; MEDICAL / General; MEDICAL / Clinical Medicine; MEDICAL / Family & General Practice